Phosphoproteomic analysis of lung tissue from patients with pulmonary arterial hypertension - Ravikumar Sitapara; TuKiet T. Lam; Aneta Gandjeva; Rubin M. Tuder; Lawrence S. Zisman (Pulmonary Circulation)
Pulmonary arterial hypertension (PAH) is a rare disorder associated with high morbidity and mortality despite currently available treatments. We compared the phosphoproteome of lung tissue from subjects with idiopathic PAH (iPAH) obtained at the time of lung transplant with control lung tissue. The mass spectrometry‐based analysis found 60,428 phosphopeptide features from which 6622 proteins were identified. Within the subset of identified proteins there were 1234 phosphopeptides with q < 0.05, many of which are involved in immune regulation, angiogenesis, and cell proliferation. Most notably there was a marked relative increase in phosphorylated (S378) IKZF3 (Aiolos), a zinc finger transcription factor that plays a key role in lymphocyte regulation. In vitro phosphorylation assays indicated that GSK3 alpha and/or GSK3 beta could phosphorylate IKZF3 at S378. Western blot analysis demonstrated increased pIKZF3 in iPAH lungs compared to controls. Immunohistochemistry demonstrated phosphorylated IKZF3 in lymphocytes surrounding severely hypertrophied pulmonary arterioles. In situ hybrization showed gene expression in lymphocyte aggregates in PAH samples. A BCL2 reporter assay showed that IKZF3 increased BCL2 promoter activity and demonstrated the potential role of phosphorylation of IKZF3 in the regulation of BCL mediated transcription. Kinase network analysis demonstrated potentially important regulatory roles of casein kinase 2, cyclin‐dependent kinase 1 (CDK1), mitogen‐associated protein kinases (MAPKs), and protein kinases (PRKs) in iPAH. Bioinformatic analysis demonstrated enrichment of RhoGTPase signaling and the potential importance of cGMP‐dependent protein kinase 1 (PRKG). In conclusion, this unbiased phosphoproteomic analysis demonstrated several novel targets regulated by kinase networks in iPAH, and reinforced the potential role of immune regulation in the pathogenesis of iPAH. The identified up‐ and down‐regulated phosphoproteins have potential to serve as biomarkers for PAH and to provide new insights for therapeutic strategies.